2018
DOI: 10.3389/fphar.2018.00884
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Metabolic Characteristics of Serum Samples in Patients With Multiple Myeloma

Abstract: Aims: This study aimed to identify potential, non-invasive biomarkers for diagnosis and monitoring of the progress in multiple myeloma (MM) patients.Methods: MM patients and age-matched healthy controls (HC) were recruited in Discovery phase and Validation phase, respectively. MM patients were segregated into active group (AG) and responding group (RG). Serum samples were collected were conducted to non-targeted metabolomics analyses. Metabolites which were significantly changed (SCMs) among groups were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Some recent works have pointed metabolic pathways and possible new therapeutic targets in MM 14 , 15 , 21 , 22 . Also, Ludwig et al 23 identified that the majority of the most represented metabolites in MGUS and MM are lipids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent works have pointed metabolic pathways and possible new therapeutic targets in MM 14 , 15 , 21 , 22 . Also, Ludwig et al 23 identified that the majority of the most represented metabolites in MGUS and MM are lipids.…”
Section: Discussionmentioning
confidence: 99%
“…LPC is described as an important low-density protein (LDL)/bioactive lipid and is responsible for the inflammatory effects of oxidized LDL on endothelial cells and stimulates basic fibroblast growth factor (bFGF) and the granulocyte–macrophage–cytokine colony-stimulating factor (GM-CSF) 40 . LPC have previously been reported as a biomolecule involved in inflammatory stimuli, promoting the release of IL-6 and other inflammatory factors, and resulting in the progression of MM 21 . Our LPC analysis showed lower plasma levels in controls versus MM and the decrease is more evident in advanced stages ISS 3.…”
Section: Discussionmentioning
confidence: 99%
“…The functional cluster analysis showed that 6 out of 8 SCMs, including LysoPC (17:0) (Figure 6A), LysoPC (20:4(8Z,11Z,14Z,17Z)) (Figure 6B), LysoPC (22:0) (Figure 6C), LysoPC (24:0) (Figure 6D), PE (P-16:0/22:4(7Z,10Z,13Z,16Z)) (Figure 6E), and SM (d18:1/22:1(13Z)) (Figure 6F), whose molecular formulas are C25H52NO7P, C28H50NO7P, C30H62NO7P, C32H66NO7P, C43H78NO7P, and C45H89N2O6P, were correlated with lipid metabolism. Among them, LysoPC (22:0) belongs to members of the lysophosphatidylcholines (LPCs), which are formed by hydrolysis of phosphatidylcholines (PCs) by the enzyme phospholipase A2 (16). The other SCMs were PE (P-16:0/22:4(7Z, 10Z, 13Z, 16Z)) and SM (d18:1/22:1(13Z)), which are essential components of membrane structure, signal transduction and lipoprotein metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Non-targeted metabolomics analysis of the serum samples in multiple myeloma (MM) has identified significantly altered metabolites that differentiate patients with advanced disease from normal samples [ 5 ]. In another study, metabolomics analysis has shown the altered levels of some metabolites, including glutamine, lysine and cholesterol, at the time of diagnosis that are returned back to normal levels upon achieving complete remission, suggesting these metabolites as the potential biomarkers of response to the therapy [ 6 ].…”
Section: Introductionmentioning
confidence: 99%